2017
DOI: 10.1016/j.molimm.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of the Man5 glycoform of human IgG3 Fc

Abstract: Immunoglobulin G (IgG) consists of four subclasses in humans: IgG1, IgG2, IgG3 and IgG4, which are highly conserved but have unique differences that result in subclass-specific effector functions. Though IgG1 is the most extensively studied IgG subclass, study of other subclasses is important to understand overall immune function and for development of new therapeutics. When compared to IgG1, IgG3 exhibits a similar binding profile to Fcγ receptors and stronger activation of complement. All IgG subclasses are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 59 publications
2
19
0
Order By: Relevance
“…A previous study indicated that the CH3 and CH2 domains of the IgG2 antibody interacted via L251 in the CH2 region and residues M428, H429, E430, and H435 in the CH3 domain . This is supported by another study that suggested that the R435 residue in the IgG3 CH3 domain may influence the CH2 domain pivot . Based on these data and our own results, we hypothesized that the substitutions made in the IgG3 CH3 domain affected the CH2 domain structure allosterically, impacting FcγRIIIa binding.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…A previous study indicated that the CH3 and CH2 domains of the IgG2 antibody interacted via L251 in the CH2 region and residues M428, H429, E430, and H435 in the CH3 domain . This is supported by another study that suggested that the R435 residue in the IgG3 CH3 domain may influence the CH2 domain pivot . Based on these data and our own results, we hypothesized that the substitutions made in the IgG3 CH3 domain affected the CH2 domain structure allosterically, impacting FcγRIIIa binding.…”
Section: Discussionsupporting
confidence: 69%
“…We further modified IgG3KV by introducing an R435H substitution that was previously shown to be important for protein A binding . R435H substitution led to the creation of IgG3KVH, with three amino acid mutations introduced into the IgG3 antibody (N392K, M397V, and R435H).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite being relatively underrepresented (approximately 5-8% of total IgG), IgG 3 deserves special attention, as in many ways, it is a unique IgG subclass. Its separation can be accomplished due to a particular feature of its amino acid sequence, that is, the presence of arginine instead of histidine at position 435 that prevents its binding to Protein A (42). Moreover, due to its superior affinity toward activating FcγRs and C1q, IgG 3 was shown to be the strongest inducer of Fc-mediated effector functions, including ADCC and CDC (23).…”
Section: Discussionmentioning
confidence: 99%
“…IgG3-based mAbs are usually not developed because of their susceptibility to proteolysis, the existence of many allotypes, and their shorter half-life in vivo. 4 The 4 IgG isotypes are highly conserved with respect to their primary sequences, presenting more than 90% similarity. 5 However, each isotype reveals a distinctive profile with regard to biological effector functions and immune complexes.…”
Section: Introductionmentioning
confidence: 99%